2010
DOI: 10.1111/j.1467-7679.2010.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Decentralisation, Governance and Health‐System Performance: ‘Where You Stand Depends on Where You Sit’

Abstract: Advocates of local government often argue that when decentralisation is accompanied by adequate mechanisms of accountability, particularly those responsive to local preferences, improved service delivery will result. From the perspective of the health sector, the appropriate degree of decentralisation and the necessary mechanisms of accountability depend upon the achievement of health system goals. Drawing on evidence from six countries (Bolivia, Chile, India, Pakistan, Philippines, Uganda), this article comes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 21 publications
2
54
0
1
Order By: Relevance
“…Mitchell and Bossert ( 2010 ) found that both fi scal and nonfi nancial resources, especially skilled and confi dent staff, are a constraint on the exercise of local discretion: '… some health-sector functions…require technical capacities that can far exceed what is possible at the local level, even for health-sector administrators' (p. 681).…”
Section: Decentralization Through Hierarchymentioning
confidence: 98%
“…Mitchell and Bossert ( 2010 ) found that both fi scal and nonfi nancial resources, especially skilled and confi dent staff, are a constraint on the exercise of local discretion: '… some health-sector functions…require technical capacities that can far exceed what is possible at the local level, even for health-sector administrators' (p. 681).…”
Section: Decentralization Through Hierarchymentioning
confidence: 98%
“…In the case of various health financing schemes in Indonesia, both public (Jamkesmas, Jamkesda, Jamsostek, Askes, ASABRI etc) and private insurances, they must be synchronised within good guidelines of comprehensive policy in order to avoid cross-purposes. This is reasonable because health is one of the most complex social-sector goods (Mitchell and Bossert, 2010), since it involves several institutions (health clinics, hospitals, pharmacies) and produces multiple products (outpatient/inpatient consultations and procedures, pharmaceuticals, public health measures).With multiple institutions of health insurance, policy coordination can facilitate different aims of various health insurance providers working together. As Ney points out, the common problem in most middle-income countries is lack of basic regulatory competences with regard to a coherent health insurance scheme.…”
Section: Analysing the Policy Coordination Ofmentioning
confidence: 99%
“…This, however, would require a change in NAADS' current focus on a few crops and input supply, as well as clarity about roles and authority at the different governance levels. Drawing a parallel to human health, Mitchell and Bossert (2010) argue that a balance is needed between centralisation of some health system functions (e.g. handling disease outbreaks, administration of health information management system) and decentralisation of others (e.g.…”
Section: Addressing the Challenges-in Uganda And Elsewherementioning
confidence: 99%